The CRM and product attribute toward purchase intention: the mediating role of brand image in Indonesia - Azzam, Fahmi Renaldy; Mangruwa, Rajiv (Enrichment : Journal of Management, 2023)
The rapid development of consumer's top choice by highlighting the value over. Through Customer Relationship Management (CRM), product attributes, and brand image, companies could provide impressions and values that distinguish them from competitors, all of which play an essential role in influencing consumer purchases. The study indicates the impact of customer relationship management and product attributes on consumer purchasing interests through brand image. The research employed a purposive sampling technique to select 150 respondents for the sample. Metode pengumpulan data melalui pemanfaatan kuesioner Google Forms. Data analysis using SmartPLS SEM Software (Structural Equation Model). The study's found that purchase intention is significantly influenced by CRM. On the other hand, Purchase intention is highly influenced by brand images, CRM, and product attribute through brand image; product characteristics have no discernible effect on purchase intention. This research suggests that CRM development, product attributes, and brand image are crucial to boosting consumer purchasing interests and making companies the top choice in today's digital age.